Pengaruh Kemajuan Teknologi Informasi dan Pengetahuan Investasi terhadap Minat Generasi Milenial di Pasar Modal - Deviyana Ludfi, Yoshe (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2025)
This research starts from the high level of capital market investors as of November 2021, the majority of which are millennials or aged 30 years and under at 59.81% but there is a low interest in investing by millennials at the Majapahit Islamic University. millennial. This has resulted in researchers analyzing the Effect of Advances in Information Technology and Investment Knowledge on Millennial Generation's Interests in the Capital Market. Applying this type of quantitative research. Analysis of the data used in this study is PLS (Partial Least Square). The population of this study were students majoring in accounting at the Majapahit Islamic University. The sample of this study amounted to 48 students. Skills technique and apply non-probability sampling method. The calculation results from the researchers show that technological advances have a significant effect on investment interest in the capital market. The results of calculations from the researchers stated that investment knowledge had a significant effect on investment interest in the capital market.